Antigenic characterization of African swine fever virus (ASFV) p30 and p54 proteins - Petrovan, Vlad (Kansas State University, 2019)
African swine fever (ASF) is a highly contagious and lethal viral disease of swine with significant socio-economic impact in the developed and developing world. In the absence of a vaccine, recent outbreaks in Europe and Asia have drawn interest in developing diagnostics tools that are critical for early detection and implementation of strict biosafety measures. African swine fever virus (ASFV) has a complex organization, containing more than 100 proteins, including those with a structural role and enzymes that are packed in the virus core for use in early infection. Among the structural proteins, p30 and p54 are also highly immunogenic, representing serological candidates for conducting ASF detection and surveillance. Production of monoclonal antibodies (mAbs) and recombinant proteins will help characterize the antigenic regions which, in turn, will lead to the development of novel diagnostic tests against this disease. In this study, a panel of mAbs was generated against recombinant p54 and p30. First, we developed a screening methodology for the resulting hybridomas using enzyme linked immunosorbent assay (ELISA) and confirmatory immunofluorescence assay (IFA) on ASFV infected cells. Our results identified five mAbs against p54 and three mAbs against p30 which were positive on both assays. Based on the screening methodology and criteria, we further characterized our mAbs by immunoprecipitation, Western blot analysis, ELISA, and immunohistochemistry (IHC) in a wide variety of tissues collected from ASFV-infected pigs. Second, the epitopes recognized by those mAbs were identified using recombinant polypeptide fragments expressed in bacteria or mammalian cells and oligopeptides. These assays identified several linear epitopes which were also recognized by sera from ASFV-infected pigs. Interestingly, the anti-p30 mAbs also recognized a region that has similar characteristics similar to an intrinsically disordered protein (IDP). Third, we evaluated the efficacy of our generated mAbs in a highly sensitive blocking ELISA, using known positive and negative serum samples. The results presented in this thesis provide valuable tools for improving ASFV diagnostics, surveillance, and vaccine development.
Keywords: African swine fever virus; monoclonal antibodies; p54; p30; diagnostic tests; epitope mapping